2020
DOI: 10.22541/au.159777189.93676219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

While Studies on Covid-19 Vaccine Is Ongoi̇ng; The Public’s Thoughts and Attitudes to the Future Covid-19 Vaccine

Abstract: OBJECTİVE In this study, we aim to investigate the thoughts and attitudes of individuals towards the future COVID-19 vaccine. METHODS This descriptive study was carried out on the web between 10/06/2020-10/07/2020. The sample constitutes all individuals above 18 years of age using social media and smartphone. The e-survey form was shared by the researchers via the web for a month, and those who completed the survey were included in the study and formed the sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Men are more likely to get vaccinated than women. Similar results are presented also in other studies with women being more reluctant to get vaccinated in comparison to men [17, 23]. Biological and lifestyle factors and immune response differs among men and women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Men are more likely to get vaccinated than women. Similar results are presented also in other studies with women being more reluctant to get vaccinated in comparison to men [17, 23]. Biological and lifestyle factors and immune response differs among men and women.…”
Section: Discussionsupporting
confidence: 89%
“…Due to their future profession, they have more knowledge about benefits of vaccines and are more awareness about their need. In a study that evaluated the attitude of population regarding future vaccination, half of them (49.7%) reported a positive willingness with students and healthcare personnel being more willingness in comparison to other occupational groups [17]. An Italian study among students concluded that 86.1% are willing to get vaccinated for COVID-19 [18] while a study in Malta among healthcare students reported acceptance rates at a level of 44.2% [19].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that both medical staffs and non-medical staffs were willing to get the COVID-19 vaccine, Perhaps the severity of the epidemic, the high infectivity of the virus and the publicity of the role of the vaccine by the media are the driving factors for them to decide to vaccinate [16]. Inconsistent results were shown in previous studies from the Indonesia, Turkey or the United States concerning the impact of demographic characteristics on the acceptance of the COVID-19 vaccine [14,15,17,18], and we found that, among the residents, respondents aged 46 to 59 were more likely to accept vaccination, while respondents' income or medical insurance may not in uence their intention as shown in the results of logistic regression analysis. This shows that people aged 46 to 59 are strongly aware that vaccines provide not only personal protection, but also family protection.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the public and private efforts, there is uncertainty regarding the number of vaccine courses available by the end of 2021 for many countries 22 ; in this context effective epidemic control can be achieved through a combination of preventive measures and gradual population vaccination 23 . On the other hand, vaccine hesitancy has been observed in different countries (USA 24 , Turkey 25 ,…), with undecided (∼30%) or refusing individuals (∼10%), and concern exists regarding their management. These percentages are not contradictory with reaching high percentages of immunity, and gradual vaccination campaigns can allow these individuals to make an informed decision.…”
Section: Discussionmentioning
confidence: 99%